2011
DOI: 10.5688/ajpe7510208
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Patient Simulation-Based Learning

Abstract: The most common types of assessment of human patient simulation are satisfaction and/or confidence surveys or tests of knowledge acquisition. There is an urgent need to develop valid, reliable assessment instruments related to simulation-based learning. Assessment practices for simulation-based activities in the pharmacy curricula are highlighted, with a focus on human patient simulation. Examples of simulation-based assessment activities are reviewed according to type of assessment or domain being assessed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…36 Simulationbased education methodologies could be especially useful when used to evaluate student performance for ACPE pre-APPE core domains and abilities. The pre-APPE core domains specifically include performance-based skills, along with knowledge, and attitudes/values/or behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…36 Simulationbased education methodologies could be especially useful when used to evaluate student performance for ACPE pre-APPE core domains and abilities. The pre-APPE core domains specifically include performance-based skills, along with knowledge, and attitudes/values/or behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It encourages the development of communication, critical-thinking, problem-solving, and teamwork skills. 6,10,11 A unique feature of high-fidelity simulation is that disease states can be replicated to allow for standardization of student learning experiences. More importantly, students can practice and perfect their patient care skills at no risk to real patients.…”
Section: Introductionmentioning
confidence: 99%
“…Following the intervention, the medication administration error rates of nurses in the study group significantly decreased from 30.8% to 4% (p ,0.001) compared to nurses in a control group whose error rates increased from 20.8% to 36.7% (p 5 0.002) over the same period of time. 14 The value of using high-fidelity manikins in pharmacy has been investigated to teach critical thinking, clinical reasoning, and problem-solving skills 7,10,15,16 ; advanced cardiovascular support 17 ; medical emergencies and critical care management 7,9 ; team-working skills and interprofessional working 16,18 ; end of life care 19 ; technical skills; and performance-based pharmacotherapy principles 15,20 In these studies, simulation was mainly used for formative assessment. Also, a variety of assessment methods was used to qualitatively and quantitatively examine the impact of simulation-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, assessment on outcomes of integrating SPs and standardized colleagues into patient communication and interprofessional interaction training, evidence-based medicine, and active learning in the pharmacy curriculum is lacking. Interprofessional relationships are important in all health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Medical schools have used SPs for decades, and their use in pharmacy is also well established. [2][3][4][5][6] The Association of American Medical Colleges performed a survey among member medical schools on simulation activities and found that more than 40% of their member medical schools train pharmacy professionals via simulation. 7 Additionally, the use of a SP has been adopted by nursing and dentistry.…”
Section: Introductionmentioning
confidence: 99%